The further shore : Sannyasa and the Upanishads, an introduction : two essays - Abhishiktananda, Swami, 1910-1973 (I.S.P.C.K., 1975)
Articles on Hindu renunciation and the Upanishads; a synthetic study from Hindu and Christian viewpoints.